Energy efficient resources allocations for wireless communication systems - Vinsensius Sigit Widhi Prabowo; Arfianto Fahmi; Nachwan Mufti Adriansyah; Nur Andini (Universitas Ahmad Dahlan, 2019)
The energy consumption level of the telecommunication process has become a new consideration in resource management scheme. It is becoming a new parameter in the resource management scheme besides throughput, spectral efficiency, and fairness. This work proposes a power control scheme and user grouping method to keep the rational energy consumption level of the resource management scheme. Inverse water-filling power allocation is a power allocation scheme that optimizes the energy efficiency by giving the power to the user which have good channel conditions. The user grouping method becomes the solution for carrier aggregation (CA) scheme that prevents edge cell user get the resources from the high-frequency carrier. This can prevent energy wastage in the transmission process. This power control scheme and user grouping method can optimize the spectral and energy efficiency without increasing the time complexity of the system.